Competency Capacity Building Needs of Crop Farmers in Soil Erosion Management in ENUGU State, Nigeria - R. U, Omeh; V. C, Asogwa; M. N, Omeje (Asian Journal of Agriculture and Rural Development, 2014)
This study sought to determine competency capacity building needs of crop farmers in soil erosion management in Enugu State, Nigeria. Four research questions guided the study. Descriptive survey research design was adopted for this study. The study was carried out in Enugu State. The population of the study was 3,562. The sample of the study was 279 drawn using quota sampling technique. The instrument used to collect data for the study was a structured questionnaire consisting of 84 items generated from review of literature. Three experts validated the instrument. Pearson product moment correlation method was adopted to determine the stability of the questionnaire items. A reliability coefficient of 0.84 was obtained. Two hundred and seventy-three copies of the questionnaire were retrieved and analyzed using weighted mean and Improvement Needed Index (INI) to answer the research questions. It was found out that crop farmers in Enugu State needed capacity building in 15 competency items in tillage, 11competency items in mulching, 10 competency items in cover cropping and 10 competency items in strip cropping for soil erosion management. It was therefore, recommended that the state government should direct the skill acquisition centres to integrate the identified competencies into their training programmes to retrain farmers in soil erosion prevention and control.